KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT. BANK MANDIRI, TBK MELALUI RASIO SOLVABILITAS, RENTABILITAS, DAN LIKUIDITAS - Ramadhan, Zulfikar Ripda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the condition of the financial performance. Bank Mandiri Tbk . Before and after the implementation of GCG through solvency ratios , profitability , and liquidity , as well as to test and analyze the significant difference level financial performance. Bank Mandiri Tbk . By using the ratio Adequency Capital Ratio , Return on Assets , Return on Equity , Net Profit Margin , and the loan to deposit ratio before and after the implementation of GCG .Â This type of research is explanatory research , the research object PT . Bank Mandiri Tbk . Methods of data collection methods through archives of the financial statements. Bank Mandiri Tbk . During the period 2002-2011 , published by the Indonesia Stock Exchange . The results of the measurement of financial performance in the test then using Paired Samples T -test . The results of this study showed that an increase in the company's financial performance after the implementation of GCG seen through the profitability ratio , whereas when seen through the solvency ratio and liquidity found a decrease in the company's financial performance after applying GCG . If the results of Paired Samples T -test , there are significant differences in the CAR and LDR in the period before and after implementation of GCG , while the ROA , ROE , and NPM found no significant differences . Keywords : Good Corporate Governance , Capital Adequency Ratio ( CAR ) , Return on Assets ( ROA ) , Return on Equity ( ROE ) , Net Profit Margin ( NPM ) , Loan to Deposit Ratio ( LDR ) .